STUDI DESKRIPTIF, MOTIVASI BELAJAR MAHASISWA PGSD’4A DALAM MENGIKUTI MATA KULIAH MANAJEMEN PENDIDIKAN UNIVERSITAS PGRI YOGYAKARTA - Mahatir Muhammad; Azamul Fadhly Noor Muhammad (STKIP Subang, 2026)
This study aims to describe the results of the analysis of Descriptive Study of PGSD'4A Students' Learning Motivation in Following Educational Management Courses at PGRI Yogyakarta University. The results of the analysis show a lack of enthusiasm and motivation of students in participating in educational management learning activities. This is because some students consider the material studied to be theoretical and less interesting, resulting in low participation in learning. In addition, differences in learning interests, learning methods used by lecturers and the learning environment can also affect student motivation in attending lectures. Student learning motivation needs attention because it has an influence on student involvement during the learning process, therefore researchers are interested in conducting this research using a qualitative approach with descriptive methods, the subjects of this study include PGSD'4A students and data collection techniques are carried out by means of observation, in-depth interviews, and documentation. Data analysis is carried out using the interactive model of miles & Huberman.